Drama activities for the development of students’ oral skills in english - López Oterino, Lorena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper aims to apply drama tasks (Gerard Finger, 2000) in the English class- room, which will add dynamism to the classroom, for the development of students’ oral competences. The aim is to work with drama in the Primary Education class- room through a series of tasks to improve oral communication, teamwork skills and to foster students’ self-esteem and confidence when producing oral language. This project addresses pupils in the sixth level of Primary Education. Theatre is a very versatile tool that provides many resources and learning, helping to improve aspects such as corporal and oral expression and cooperative work.